The Covid-19 crisis response helps the poor: The distributional and budgetary consequences of the UK lock-down - Patryk Bronka; Diego Collado; Matteo Richiardi (University of Essex, Institute for Social and Economic Research (ISER), 2020)
We nowcast the economic effects of the Covid-19 pandemic and related lock-down measures in the UK and then analyse the distributional and budgetary effects of the estimated individual income shocks, distinguishing between the effects of automatic stabilisers and those of the emergency policy responses. Under conservative assumptions about the exit strategy and recovery phase, we predict that the rescue package will increase the cost of the crisis for the public budget by an additional 26 billion, totalling over 60 billion. However, it will allow to contain the reduction in the average household disposable income to 1 percentage point, and will reduce poverty rate by 1.1 percentage points (at a constant poverty line), with respect to the pre-Covid situation. We also show that this progressive effect is due to the increased generosity of Universal Credit, which accounts for only 20% of the cost of the rescue package.
Keywords: D31; I38; 330; Covid-19; Job Retention scheme; Self-employment Income Support Scheme; Universal Credit; poverty; public budget